(untitled) (Dhaka University Journal of Biological Sciences, 2012)
Limnological investigation on a conserved man?made lake located in the Safipur Ansar and VDP Academy, Gazipur district has been carried out between July, 2008 and May, 2009. Thirteen limnological parameters were measured mostly at fortnight intervals and their annual and seasonal fluctuations were observed. The lake water was slightly alkaline in nature having a monthly mean pH range 7.26 ? 7.91. The water temperature varied from 18 ? 32°C. Soluble reactive phosphorus, soluble reactive silicate and nitrate nitrogen ranged from 9.22 ? 154.57 ?g/l, 2.52 ? 17.06 and 0.17 ? 187 mg/l, respectively. DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11511 Dhaka Univ. J. Biol. Sci. 21(2): 131-140, 2012 (July)